Long-term stability of UHMWPE fibers. (April 2015) - Forster, Amanda L.; Forster, Aaron M.; Chin, Joannie W.; Peng, Jyun-Siang; Lin, Chiao-Chi; Petit, Sylvain; Kang, Kai-Li; Paulter, Nick; Riley, Michael A.; Rice, Kirk D.; Al-Sheikhly, Mohamad
Abstract: The performance of ultra-high molecular weight polyethylene (UHMWPE) fibers for ballistic protection is predicated on the development of a highly aligned molecular structure that allows the polymer to exhibit a superior strength in the axial direction of the fiber. However, even an ideal molecular structure will be subjected to degradation during use, which can reduce the high strength of these fibers, and impact their ability to protect the wearer. In this work, the long term stability of UHMWPE fibers are investigated and the activation energy for this mechanism was calculated to be approximately 140 kJ/mol, in agreement with previous reports. The inclusion of accelerated aging temperatures that encompass the alpha-relaxation temperature introduced physical effects in addition to oxidative degradation that complicate a simple explanation of the changes in properties. Assuming that the shift factors that were used in this analysis are correct, it would take approximately 36 years for the tensile strength of this UHMWPE yarn to fall by 30% at 43 °C. Changes in the oxidation index of this material due to aging are also studied using Fourier Transform Infrared (FTIR) Spectroscopy, and no simple correlation between the retained strength and the oxidation index was found.